Hedging Winner's Curse with Multiple Bids: Evidence from the Portuguese Treasury Bill Auction - Gordy, Michael B. (The Review of Economics and Statistics, 1999)
Auctions of government securities typically permit bidders to enter multiple price-quantity bids. Despite the widespread adoption of this institutional feature and its use by bidders, the motivations behind its use and its effects on auction outcomes are not well understood theoretically and have been little explored empirically. This paper proposes that bidders use multiple bids to adjust for winner's curse: By spreading her bids, a bidder aligns her outcome more closely to the aggregate outcome of the auction. This hypothesis is tested using bidding data from treasury bill auctions in Portugal. I find that, ceteris paribus, a bidder submits a greater number of bids and disperses prices on these bids more widely when there is a greater potential for winner's curse. In particular, both these measures of bid-spreading increase with the volatility of market interest rates and the expected number of participating well-informed bidders.